Improving nutrient values of solid heavy phase for corn substitute in poultry diet - Sinurat, A.P; Purwadaria, T; Bintang, I.A.K; Pasaribu, T (Indonesian Journal of Animal and Veterinary Sciences, 2007)
Solid heavy phase (SHP), a by product material of palm oil factory obtained by ceramic filtration from liquid waste could be produced approximately 2 million tons/year. The by product has a potential for substituting corn in poultry feed. A series of experiment was carried out to improve nutrient value of the SHP in order to obtain a feedstuff that can substitute corn in poultry feed. The SHP was processed by either fermentation or enzymatic process. The product was then dried and analysed for its nutrient values. Fermentation process was carried out by altering the dry matter of the substrate (40 or 50%), while enzymatic process was carried out by altering the dose and kind of enzymes used. The process that produced best nutrient values was considered for producing materials for a feeding trial. In this trial, the products were used in diet formulation to substitute 25 or 50% of the corn included in the control diet. The results showed that the fermentation processed could be conducted with dry matter of substrate at either 40 or 50%. The fermentation process significantly improved the nutrient values of the SHP as shown by decreasing the crude fibre and increasing the crude protein, amino acids and the ME value. The results also showed that the Balitnak enzyme (BS4) was optimum when added at 10 ml/kg dry matter SHP, while the commercial enzyme (EK) was optimum at level of 2 g /kg dry matter SHP. Results of feeding trial showed that 25% of corn in layer diet could be substituted with dried SHP or SHP + enzymes. This substitution tended to improve performances (egg production, egg weight and FCR) of the laying hens. Substitution of 25 or 50% corn with the fermented SHP tends to reduce the performance of the layinghens. Similar trend also occurred when 50% of the corn was substituted with the enzymaticly processed SHP. Key Words: Solid Heavy Phase, Palm Oil Waste, Fermentation, Enzymes, Laying Hens